Integrasi Ilmu Islam dalam Pembelajaran di Madrasah Ibtidaiyah - Mirna Astuti; Sedya Santosa (Program Studi Pendidikan Guru Madrasah Ibtidaiyah (PGMI) Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2024)
Educational problems that occur due to the lack of good behavior or good morals in individuals are a problem for the world of education. Given the success in the formation of a good personality will have an impact on the goodness of the individual including the improvement of the quality of education. For this reason, the application of Islam in education plays a major role in this matter. Research on the implications and implementation of Islamic science to Madrasah Ibtidaiyah with qualitative research with library research methods that are carried out by examining various references related to this research. The results of this study concluded that the application of Islam in education can be done through learning in the classroom or outside the classroom. The efforts made by educators in this application are to continue to improve their abilities and continue to learn how to connect Islam with learning at the Madrasah Ibtidaiyah level, and teachers always control or self-control to always be a good example for students.